Medieval letters: Other languages - Språkbanken Text (University of Gothenburg, 2024)
Charters written in other languages, from the Diplomatarium Suecanum (Svenskt Diplomatariums huvudkartotek, SDHK)

Från Riksarkivet.
Medeltidsbrev: Övriga språk
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik